Relationship between Respiratory Function and the Strength of the Abdominal Trunk Muscles Including the Diaphragm in Middle-Aged and Older Adult Patients - Yuki Kurokawa; Satoshi Kato; Noriaki Yokogawa; Takaki Shimizu; Hidenori Matsubara; Tamon Kabata; Satoru Demura (Journal of Functional Morphology and Kinesiology, 2024)
Objectives: Respiration plays an important function in sustaining life. The diaphragm is the primary muscle involved in respiration, and plays an important role in trunk stabilization. Although it has been reported that respiratory function is important for trunk muscle stability, the correlation between respiratory function and abdominal trunk muscle strength remains undetermined. This study aimed to clarify this correlation among middle-aged and older patients. Methods: This observational study included 398 patients scheduled for surgery for degenerative conditions of the lower extremities. Respiratory function was evaluated using forced vital capacity and forced expiratory volume in 1 s measured using spirometry. Each patient underwent a physical function test before surgery, which included the assessment of the abdominal trunk muscle strength, grip power, knee extensor strength, one-leg standing time, and gait speed. Correlations between abdominal trunk muscle strength, respiratory function, and physical function were evaluated. Results: Abdominal trunk muscle strength was significantly correlated with forced vital capacity, forced expiratory volume in 1 s, grip power, knee extensor strength, one-leg standing time, and gait speed. Multiple linear regression analyses revealed that sex, forced vital capacity, forced expiratory volume in 1 s, and knee extensor strength were significant factors associated with abdominal trunk muscle strength. Conclusions: In middle-aged and older patients, abdominal trunk muscle strength including that of the diaphragm, is associated with forced vital capacity and forced expiratory volume in 1 s.